PERLINDUNGAN HUKUM DATA PRIBADI KARYAWAN DALAM SISTEM HR DIGITAL PADA APLIKASI HRIS TALENTA DI ERA DIGITALISASI INDUSTRI - Bahiyah Bahiyah (SINERGI : Jurnal Riset Ilmiah, 2026)
The implementation of the Talenta Human Resource Information System (HRIS) is a form of digitalization of human resource management aimed at improving the efficiency and effectiveness of employment administration. However, the use of this system has direct implications for the management and protection of employee personal data, thus requiring an adequate legal basis and protection mechanisms. This study aims to analyze the legal protection of employee personal data in the implementation of Talenta HRIS and the company's efforts to ensure the fulfillment of employee rights. The results show that Law Number 27 of 2022 concerning Personal Data Protection, Law Number 11 of 2008 concerning Electronic Information and Transactions and its amendments, and laws and regulations in the employment sector have provided a legal basis for the protection of employee personal data.However, in practice, various challenges remain, including cybersecurity risks, excessive data collection practices (over-collection), digital system integration, and low employee awareness of personal data protection. Therefore, companies are required to implement comprehensive internal policies, adequate technical safeguards, ongoing employee education, compliance audits, and oversight by a Data Protection Officer (DPO). With consistent implementation of these efforts, the use of Talenta HRIS will not only improve the efficiency of human resource management but also align with the principles of legal protection and legal certainty for employees in the era of digital industrial relations.